2015
DOI: 10.1007/s10616-015-9869-6
|View full text |Cite
|
Sign up to set email alerts
|

Binucleated HeLa cells are formed by cytokinesis failure in starvation and keep the potential of proliferation

Abstract: Many cytological studies have reported that the numbers of binucleated cells were elevated in various tumors. However, binucleated cells are observed in not only malignant tumors but also normal tissues. Thus, the clinical significance of binucleated cells is controversial. Here we attempted to elucidate the characteristics of binucleated HeLa cells using time-lapse microscopy. To examine the frequency, viability, proliferation, and formation mechanism of binucleated cells, we grew HeLa cells on chamber slides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This indicated that STK16-IN-1 exerted its effect through STK16 kinase. We then screened a panel of mutations 16 in the STK16 kinase ATP binding pocket including the L98F, L98Q, G104 (N, D, E), and F100C and found that STK16 F100C mutation could significantly abolish STK16-IN-1's inhibitory effect (Supporting Figure 9). Transformation of this mutant into HeLa cells with a GFP-FLAG labeled STK16 kinase showed that the G2/M-phase cell cycle arrest effect of STK16-IN-1 was rescued (Figure 4E,F).…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…This indicated that STK16-IN-1 exerted its effect through STK16 kinase. We then screened a panel of mutations 16 in the STK16 kinase ATP binding pocket including the L98F, L98Q, G104 (N, D, E), and F100C and found that STK16 F100C mutation could significantly abolish STK16-IN-1's inhibitory effect (Supporting Figure 9). Transformation of this mutant into HeLa cells with a GFP-FLAG labeled STK16 kinase showed that the G2/M-phase cell cycle arrest effect of STK16-IN-1 was rescued (Figure 4E,F).…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…On the other hand, the number of binucleated cells in the progerin group is higher than that of the WT lamin A group, regardless of flow condition or shear level ( Figures 6E–G ). Binucleation appears to be a hallmark of progerin-expressing ECs, and shear-induced binucleation could be a result of cytokinesis failure in progerin-expressing ECs ( Nishimura et al, 2016 ). No significant changes were observed in WT lamin A-expressing cells under different flow conditions, indicating that normal shear stress did not prevent these cells from entering the G2/M phase.…”
Section: Resultsmentioning
confidence: 99%
“…We also found a higher average frequency of PNCs in participants with obesity, which is indicative of increased cytokinesis failure. Cancer cell lines have been used to demonstrate the mutagenic consequences of binucleated cells [ 96 ]. In a recent review, tetraploidy and cytokinesis failure have been evaluated as mechanisms for aneuploidy in subsequent mitotic cycles.…”
Section: Discussionmentioning
confidence: 99%